2022
DOI: 10.1292/jvms.22-0335
|View full text |Cite
|
Sign up to set email alerts
|

Hot spring bathing accelerates wound healing and enhances heat retention effect in guinea pigs

Abstract: This study aimed to demonstrate the effects of hot springs on wound healing and heat retention by performing comparative experiments with tap water. The hot spring water used in this study was from an alkaline hot spring that was rich in sodium and chloride ions and exhibited high reducibility. Guinea pigs were divided into a hot spring bathing group and a tap water bathing group, and a bathing test was conducted for eight consecutive days. A comparison of the plasma amino acid composition between the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Furthermore, in the aquaria where the study was conducted, a water temperature difference of 10–15°C was noted between summer and winter, and wound healing was significantly faster during the warmer summer season. Several studies have shown that heating the skin surrounding the wound site improves blood flow by dilating the capillaries in the wound region, hence accelerates wound healing (Derakhshandeh et al, 2018; Inaka & Kimura, 2022; Phillips, 2000). Therefore, a similar mechanism may be involved in wound healing in the common bottlenose dolphins used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the aquaria where the study was conducted, a water temperature difference of 10–15°C was noted between summer and winter, and wound healing was significantly faster during the warmer summer season. Several studies have shown that heating the skin surrounding the wound site improves blood flow by dilating the capillaries in the wound region, hence accelerates wound healing (Derakhshandeh et al, 2018; Inaka & Kimura, 2022; Phillips, 2000). Therefore, a similar mechanism may be involved in wound healing in the common bottlenose dolphins used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The valorization of geothermal energy in different areas of agriculture is also discussed in studies such as Kępi ńska, 2021, and Skrzypczak et al, 2021 [40]. The new forms of valorisation of geothermal water outlined after the Revolution, wellness and spa, and the skincare sector are also discussed in other research [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates trends for more sustainable and environmentally friendly geothermal water supply systems for heating [35]. More studies have discussed the alternative use of geothermal water; in addition to balneology, it is used as a dermatological treatment in the cure of various conditions, through its anti-inflammatory effects and acceleration of the healing process [36][37][38][39]. Another form of valorisation that has not been researched enough is the application of geothermal energy in different areas of the agricultural sector, such as irrigation, heating of greenhouses and soil, drying of agricultural products, and cultivation of algae [40,41].…”
Section: Literature Reviewmentioning
confidence: 99%